Synthesis and characterization of gallium oxide nanocrystals - Iltanen, Kari (My University, 2022)
In this thesis a method for synthesizing gallium oxide nanocrystals was investigated. This is a new technique and therefore its properties are not well known. By utilizing this method, synthesis of gallium oxide nanocrystals by placing GaAs substrate into hot water is simpler than other methods used so far. Theory of nanocrystal growth is used to understand what processes are involved in the synthesis. The theory of crystal growth is divided into classical and non-classical parts, where former involves monomer by monomer addition and latter involves intra- and interparticle interactions. This includes interaction between water and substrate and other reactions that could be involved in the synthesis. Gallium oxide nanocrystals have many applications in optoelectronics and power electronics due to its ultra wide bandgap, high breakthrough voltage and chemical inertness. Some potential applications are deep UV photodetectors, photocatalysis and sensors. In the experimental part, the first step was to determine properties of nanocrystals synthesized with no additional treatment to establish a baseline, which later samples will be compared to. Later pretreated substrates were used to see how changes in the surface properties of the substrate could have affected the end result of the synthesis. One of the goals was to find ways to control size distribution and amount of nanocrystals per unit area. For this purpose multiple pre-synthesis treatments for the substrate were tested, such as roughening and seeding. Surface roughness was investigated by atomic force microscopy. Elemental analysis with X-ray photoelectron spectroscopy and electron energy dispersive spectroscopy was used as needed to determine elemental composition of some features and surfaces. Synthesized nanocrystals were measured with scanning electron microscope (SEM). For each sample size distribution, morphology, fraction of the surface covered by nanocrystals were determined. Most synthesized nanocrystals were quite wide, around seven hundred nanometres, but one modification to the synthesis process reduced the widths of typical nanocrystals by tens of percent. Typical aspect ratios were between five and ten. X-ray diffraction was used to investigate crystal structure of the nanocrystals before and after ultra high vacuum heating.
Keywords: nanocrystals, GaAs, characterization, synthesis, gallium oxide, GaOOH